DIRECTIVE LANGUAGE FUNCTION IN “BEFORE I FALL” MOVIE SCRIPT” - Loi, Kristina (Research on English Language Education, 2023)
This research was aimed to analyze the types of directive language function in Before I Fall Movie Script and describe the meanings of directive language function in Before I Fall movie script. This research designed by using qualitative research with descriptive qualitative approach. The data was obtained from movie script of Before I Fall. The data was collected by downloading Before I Fall movie script, finding the words, phrases or sentences which consist of directive language function, the analyze it which found out. In analyzing the data, the researcher used theory of Miles, Huberman, & Saldaria (2014:31-33). To examine the credibility of this study the researcher used triangulation such as data triangulation, investigator triangulation and theory triangulation. Based on the result, the researcher found three of the types of directive languages function, they are 25 commands, 19 requests, 11 suggestion. It can be concluded that the dominant directive used in “Before I Fall” movie script is commands are 25. Based on the conclusions, the research would give contribution for the college students especially at English Department, that script of Before I Fall movie can be used as a material college students to broaden and develop their knowledge about directive language function and three of the types directive language function in Before I Fall movie script. And also for the readers or for the next researcher, the researcher suggested this research can be used as a conception and reference in conducting research related to directive language function.